The Role of the Family Environment in Shaping the Prosocial Behavior of Early Childhood in Lakambau Village, Batauga District, South Buton Regency - Waode Lusiyana; Ria Safaria Sadif; Sitti Misra Susanti (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2022)
This study aimed to determine "The role of the family environment in shaping the prosocial behavior of early childhood in Lakambau Village, Batauga District, South Buton Regency". This research used descriptive qualitative research, which studies existing problems and applicable work procedures. This qualitative descriptive study aimed to describe what is currently happening. The unit of analysis used in this study was the family environment. The research results and the discussion indicated the role of the family in shaping the prosocial behavior of early childhood in the Lakambau Village, Batuaga District, South Buton Regency. This can be seen from the results of the data obtained in the Batuatas environment that the role of the family by providing examples, motivation, a sense of security/protection, and continuous supervision could shape the prosocial behavior of early childhood. The formation of prosocial behavior such as showing enthusiasm, obeying the applicable rules of the game, and showing empathy has begun to develop according to expectations and is relatively increasing.